Estimation of above-ground biomass and carbon in temperate forests of southern Mexico - Guzmán-Santiago, Juan Carlos; De los Santos-Posadas, Héctor Manuel; Vargas-Larreta, Benedicto; Gómez-Cárdenas, Martín; Marroquín-Morales, Pablo (Ecosistemas y Recursos Agropecuarios, 2024)
Forest inventories are tools that allow the collection and recording of information for the estimation of volume and biomass in order to determine carbon sequestration in forest biomass using regression techniques. The objective of the study was to generate allometric equation parameters that accurately estimate the biomass and total aboveground carbon content of 25 temperate species from UMAFOR 2012, San Juan Quiahije, Oaxaca. Circular sampling sites of 1000 m2 were established, where the normal diameter and total height of 16 863 trees of 25 species were taken; subsequently, biomass and aboveground carbon content were estimated through allometric equations, using SAS software. The simultaneous potential equation had the best goodness of fit, where the adjusted coefficient of determination (R2adj) was over 87% for total biomass, while the total carbon estimate had an R2adj of 99% for all species. Pinus maximinoi had the highest average biomass (35 971.85 and 2 922.03 kg) and carbon content (17 985.92 and 1 462.01 kg) in branches and stems, respectively.
Keywords: Biomass, carbon content, diameter, height, forest inventory.